Pengaruh Metode Pembelajaran Gallery Walk Berbasis Multi Produk terhadap Nilai Gotong Royong dalam Pembelajaran Pendidikan Pancasila Bab IV Persatuan dan Kesatuan Wilayah Kabupaten/kota di SD Negeri Rejosari 01 Kelas VC - Nada Etika Hapsari; Nia Sintia; Aries Tika Damayani; Sri Nurhayati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The background of this study is that the fifth-grade students class VC of SDN Rejosari 01 are already able to understand abstract concepts such as unity. However, they still require real-life experiences rather than purely theoretical knowledge, with a method that can connect the concept of unity to everyday experiences in the district/ city environment. The gallery walk method with multi product outcomes provides students with the opportunity to present their work according to their individual abilities. This process fosters the values of cooperation. According to Noppitassari et al. (2023), the indicators of cooperation are teamwork, coordination, empathy, sharing, and maintaining good relationships. This study aims to determine the effect of the gallery walk method with multi product outcomes on the cooperative values of fifth-grade students class VC at SDN Rejosari 01 in the subject of Pancasila Education, Chapter IV: Unity and Cohesion in the district/ city environment. The research used a quantitative approach with a pre-experimental design in the form of a one group pre test post test design. The Population consisted of class VC students at SDN Rejosari 01, with a sample of 28 students. The data collection techniques included tests (pre test and post test) and questionnaires. The data analysis technique used inferential analysis with parametric statistics, specifically the paired samples t test, assisted by SPSS Statistics 26. The results of this study show that the use of the gallery walk method with multi product outcomes has an effect on cooperative values in Pancasila Education, Chapter IV: Unity and Cohesion at SDN Rejosari 01. There was a significant difference between learning outcomes before and after the implementation of the method. This difference was influenced by the pre test and post test scores. The paired samples t test produced a significance value of 0,000 < 0,05, which indicates that there is a significant difference between the pre test and post tes results. Therefore, it can be concluded that the gallery walk method with multi product outcomes has a positive effect on cooperative values in Pancasila Education, particularly in the context of unity and cohesion at the district Keywords: gallery walk, multi product, cooperative values, Pancasila Education